PENERAPAN POLA ASUH OTORITER ORANG TUA PADA PRESTASI BELAJAR SISWA DI MIS RAUDLATUL HASAN WONOMERTO - Mukarromah, Faizatul; Fadilah, Yulina; Khosiah, Nur (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research applies Qualitative Field Research, in this case there are several stages, namely: planning, implementation, observation, and data analysis stages. The reason the author made the journal "Application of Parental Authoritarian Parenting to Student Learning Achievement at MIS Raudlatul Hasan Wonomerto" was because he wanted to expand knowledge about authoritarian parenting which according to some people has many disadvantages than advantages. Because according to the author authoritarian parenting is also good in its application to educate children. 1st grade students of MIS Raudlatul Hasan Wonomerto in the 2022-2023 academic year, which numbered 21 students. There are several ways of collecting data, namely starting from observation, documentation and conducting questionnaires or questionnaires. Then the researcher makes a reduction by taking the necessary data and then the data is collected to be analyzed to get the results of the research that has been done. In the results of the study it can be concluded that, the Application of Parental Authoritarian Parenting on student learning achievement can have a good and bad effect on children. Because children also need affection from parents, children who are too restrained will show a rebellious spirit. But as parents must also understand what children need and want, because sometimes even though according to parents authoritarian parenting is good for children sometimes children want the opposite.